Presurgical Evaluation by a Health Behavior Psychologist Can Effectively Delineate Patient-Specific Barriers that Impact Treatment Outcomes after Osteochondral Allograft Transplantation - Rucinski, Kylee; Stucky, Renee; Jones, Felicia; Stannard, James P.; Nuelle, Clayton W.; Cook, James L. (The Journal of Knee Surgery, 2025)
Osteochondral allograft transplantation (OCAT) is an effective treatment option for young, active patients with full-thickness articular cartilage defects, but long-term success is limited by treatment failures often linked to nonadherence to postoperative protocols. Validated methods for preoperative identification of patients at risk for nonadherence and/or poor outcomes following OCAT are limited. This study aimed to characterize the ability of a health behavior psychologist (HBP) to preoperatively delineate patient-specific barriers associated with nonadherence and failure following OCAT. Patients were prospectively enrolled in a lifelong, institutionally approved registry. Patients were eligible for inclusion if they had a preoperative evaluation with an HBP. Demographic, biopsychosocial, patient-reported outcomes surveys, and adherence status were collected. Risk domains (low, medium, high) were assigned by the HBP based on the presence and severity of barriers identified during HBP evaluations. OCAT patients (n = 99) were evaluated and assigned a risk domain: (low-risk [n = 41], medium-risk [n = 44], high-risk [n = 14]). Patients in medium- and high-risk cohorts reported significantly more barriers, including mental health issues, limited social support, and high-demand occupations, compared with low-risk patients. Nonadherence rates were significantly higher in medium- and high-risk cohorts; however, nonadherence was not significantly associated with treatment failure. The low-risk cohort reported better mental health and satisfaction outcomes, whereas medium- and high-risk patients had worse physical health outcomes. Preoperative HBP evaluations effectively identified patient-specific barriers to adherence, enabling targeted interventions to improve OCAT surgery outcomes. Integrating behavioral health support into orthopaedic care may improve adherence, highlighting the need for broader implementation and further studies.Level of Evidence 2, prospective cohort study
Keywords: orthopaedics; nonadherence; biopsychosocial; mental health; behavioral health